Factors That Influence Financial Statement Fraud Using The Fraud Diamond Model - Ady Setyo Nugroho (Jurnal ASET (Akuntansi Riset), 2022)
This study aims to obtain an empirical evidence about detection of the financial statement fraud accordance with the fraud diamond theory perspective that developed by Wolfe and Hermanson (2004). Proxy of independent variable that is the fraud diamond theory with four fraud risk factor is the factor of pressure proxied by leverage ratio, while the factor of opportunity was proxied by asset composition ratio, the factor of rationalization was proxied by audit quality, and the factor of capability proxied by percentage of director with accounting and finance education background, respectively. The samples that used in this study were 534 manufacturing companies that were listed in Indonesia Stock Exchange (IDX) in the period of 2013 until 2017. Secondary data were used in the form of annual reports of every companies. Hypothesis testing in this study was conducted by using logistic regression analyses with SPSS 20 software. The results of this study showed that variables such as pressure (proxied by leverage ratio), opportunity (proxied by asset composition ratio), and rationalization (proxied by audit quality) could be used to predict the financial statement fraud.